Seepage Analysis on the Surface Layer of Multistage Filled Slope with Rainfall Infiltration - Bingxiang Yuan; Zengrui Cai; Mengmeng Lu; Jianbing Lv; Zhilei Su; Zuqing Zhao (Advances in Civil Engineering)
Based on the theory of rainfall infiltration, the surface infiltration model of multilevel filled slope was established by using the SEEP/W module of GeoStudio. The changes of the volumetric water content (VWC) and pore water pressure (PWP) in the surface of the slope during the rainfall infiltration were analyzed, and the influence of the change of the rainfall conditions on the VWC and PWP was considered. The analysis showed that VWC and PWP increased when the rain fell, and the growth rate of the higher feature point was higher. The affected area was concentrated on the upper part of the surface about 0.75 m. With the increasing of rainfall intensity, the slope surface getting to transient saturation state was quick, and the time of the PWP increasing to 0 among the feature points of same elevation was shortened. Meanwhile, the PWP presented a positive value, and as the infiltration depth increased, the transient saturation region expanded. The safety coefficient of the multistage filled slope was continuously reduced; after the stop of rainfall, the VWC and the PWP decreased, and the decline rate of the higher feature points was higher. In addition, the PWP of the lower part increased, and the safety factor of the slope presented a trend of rebound.